Basic Concepts of Organization: A Literature-based Qualitative Study - Yuliati, Yuliati; Afif, Muslihul; Ni’mah, Shofwatun; Hidayah, Khalimatul; Waluyo, Waluyo (Jurnal Penelitian Pendidikan, 2025)
The existence of organizations is essential because human beings, as social creatures, cannot fulfill all of their needs individually. This study examines the fundamental concepts underlying organizations. Its primary objective is to identify and understand the key elements encompassed within the basic framework of organizational theory. Employing a qualitative methodology with a literature review approach, the research draws upon digital literacy sources and other relevant data pertinent to the topic. Through analyzing various scholarly references, particularly conceptual frameworks and the Qur'anic perspective on organizational principles, this study explores definitions, essential components, organizational management principles, structural elements, and the broader social role of organizations. The findings indicate that robust theoretical foundations support organizational theory and harmonize the spiritual values embedded in Islamic teachings. Findings from the literature also emphasize that an ideal organization is not solely built upon structural systems, procedures, and work efficiency, but also supported by rooted values of ethics, morality, and spirituality deeply.